The regulation of antiviral activity of interferon epsilon - Zhao, Fu-Rong; Wang, Wei; Zheng, Qin; Zhang, Yan-Ge; Chen, Jianming (Frontiers in Microbiology, 2022)
Interferon epsilon (IFN-ε) is a type I interferon. It has been identified in many species, and some biological properties have also been revealed, such as antiproliferative, anti-tumor, and antiviral effects, which are much weaker than those of IFN-α. It has been shown to play a role in mucosal immune and bacterial infections and in preventing certain sexually transmitted diseases, such as the human immunodeficiency virus. This article reviews the known activity of IFN-ε, particularly in some viruses. In general, this review provides a better understanding of the effective treatment of IFN-ε in the future.